Surgical treatment for recurrent solitary fibrous tumor invading atlas. Issue 11 (9th April 2014) - Tsutsumi, Nao; Kojima, Yasutaka; Nishida, Kotaro; Maeno, Koichiro; Kakutani, Kenichiro; Kawakami, Fumi; Kanzawa, Maki; Itoh, Tomoo; Otsuki, Naoki; Nibu, Ken‐ichi; Andersen, Peter
Abstract Background Solitary fibrous tumor (SFT), a rare neoplasm, usually originates in the pleura. Extrapleural SFTs occasionally occur in the head and neck. Methods In this study, the extirpation of a rare case of recurrent SFT invading the atlas is discussed. Results Ten years after surgical resection of an SFT in the right parapharyngeal space, the patient returned with a complaint of swelling sensation in the right neck. MRI and CT showed an enhanced lobulated mass invading the right lateral C1 vertebral body and canal and encasing the right vertebral artery. Extirpation of the recurrent tumor with a combined transcervical and midline posterior approach was successful. The surgical margin was negative for cancer and the postoperative course was uneventful. Conclusion Although an SFT is generally benign, recurrence can occur even after several years, therefore, careful long‐term follow‐up is essential for early detection. A combined transcervical and midline posterior approach proved useful for resection of the atlas body. © 2014 Wiley Periodicals, Inc. Head Neck 36: E121–E124, 2014